Organoleptic and Total Plate Count (TPC) Tests of Lanolin Lipstick Made from Sheep Wool with the Addition of Red Dragon Fruit (Hylocereus polyrhizus) Peel Extract - Desse Martha Pardosi; Nurzainah Ginting; Rita Rosmala Dewi (Jurnal Peternakan Integratif, 2025)
The peel of red dragon fruit possesses potential as a source of natural colorant rich, which provides a bright and stable red color for an environmentally friendly alternative compared to synthetic dyes. This study aims to analyze the organoleptic quality and Total Plate Count (TPC) and irritation test of lipstick formulations utilizing lanolin from sheep wool and the addition of red dragon fruit peel extract (Hylocereus polyrhizus). The study's background is the potential of lanolin as a moisturizing base for lipstick and red dragon fruit peel extract as a natural coloring alternative to synthetic dyes. Lipstick was formulated with varying concentrations of red dragon fruit peel extract (0%, 20%, 40%, and 60%) to observe the effect on product quality. The research includes organoleptic tests (color, aroma, texture, preference) and TPC tests to analyze the number of microorganisms in the lipstick also irritation test. The results showed that the addition of red dragon fruit peel extract significantly influenced the organoleptic properties and microbial safety of the lipstick. The formulation with 60% extract (P3) exhibited the most appealing color, a pleasant aroma preferred by panelists, and favorable texture. Furthermore, the TPC test indicated that the P3 formulation had the lowest microbial count, suggesting better microbiological safety. The irritation test also confirmed that the 60% extract addition caused no signs of irritation.The treatment with the addition of 60% red dragon fruit peel extract (P3) showed the best results